EFFORTS TO IMPROVE IPA LEARNING OUTCOMES THROUGH THE USE OF COOPERATIVE LEARNING MODELS IN CLASS VII A STUDENTS MTs STATE 8 TASIKMALAYA - Iwan, Abang (Jurnal Metaedukasi: Jurnal Ilmiah Pendidikan, 2020)
Efforts to Improve Learning Outcomes of Natural Sciences Through the Use of the Tife STAD Cooperative Learning Model in Class VII A Students of MTs Negeri 8 Tasikmalaya. This study aims to determine student learning outcomes between Tife STAD Cooperative Learning in Natural Sciences. The study was conducted at MTs Negeri 8 Tasikmalaya by taking a sample of one class, class VII A. The research method used was the Tife STAD Cooperative Learning Model, a research model using data collection instruments for student learning outcomes through group discussion. Based on the results of data processing and discussion of research results that have been conducted by researchers, it can be concluded as follows: In Cycle I the average score of science learning outcomes is 22,159 (73.86%) of the ideal score that can be achieved by students 20 (100%) and the standard deviation is 3.108. In the second cycle the average score of science learning outcomes is 24.316 (81.05%) of the ideal score that can be achieved is 30 (100%) and the standard deviation is 2.689. STAD model Cooperative Learning in science learning can improve student activities and learning outcomes. Based on the findings above, the author can suggest, advanced researchers can integrate several learning models that can be integrated into the STAD Type Cooperative Learning model so that the success rate will be even greater. A contextual approach to STAD Type Cooperative Learning can be an alternative as an effort to improve the completeness of student learning outcomes and activate the learning process. To overcome the problems mentioned above, it is necessary to strive for a learning approach that can be used to make learning more active, which is a learning concept to help teachers link material taught with students 'daily lives and encourage students to make connections between students' initial knowledge and application in life as family and community members. STAD Cooperative Learning Type because this model is the simplest cooperative learning model so that students can more easily understand and do learning in groups. The STAD cooperative learning model is very effective to be used for science learning. The results showed that there were differences in student learning outcomes in science lessons using the Tife STAD Cooperative Learning Model. learning outcomes in classrooms that are treated with such learning better.